ZNF300 tight self-regulation and functioning through DNA methylation and histone acetylation - Feng-Juan Yan; Jingyi Fan; Zan Huang; Jun-Jian Zhang (Cell & Bioscience, 2017)
Abstract Background Accumulating evidence demonstrates that the KRAB-ZNFs involve in various biological processes. As a typical member of KRAB-ZNFs, dysregulation of ZNF300 contributes to multiple pathologies such as leukemia and cancer. However, mechanisms underlying ZNF300 tight regulation and its pathophysiological function remain largely unknown. Methods The effect of ZNF300ZFR on gene transcriptional activity was measured by Dual luciferase reporter system. ChIP-PCR assay were performed to detect the enrichment of ZNF300 protein and H3K9Ac in the ZNF300 gene. Co-immunoprecipitation assays followed by western blot were performed to detect the interaction between ZNF300 and KAP1. The DNA methylation in the ZNF300 gene promoter was analyzed by BSP. ZNF300 function on K562 cell differentiation was analyzed by flow cytometry. Results In this study, we found that the zinc finger domain-encoding region (ZFR) of ZNF300 functioned as a repressor possibly by mediating DNA methylation and ZNF300 bound to its ZNF300ZFR, suggesting a potential auto-inhibition mechanism. To support this, DNA methylation inhibition upregulated ZNF300 expression and ZNF300 overexpression inhibited endogenous ZNF300 expression. More importantly, DNA methylation inhibition restored megakaryocyte differentiation in K562 cells suppressed by ZNF300 downregulation, suggesting an important role of DNA methylation in ZNF300 function. Interestingly, ZNF300 knockdown restored global H3K9Ac that was reduced in K562 cells undergoing megakaryocyte differentiation. Conclusions Our study revealed novel features of ZNF300 that possibly mediate its regulation and function by modulating epigenetic modifications.